2017
DOI: 10.1002/pssb.201700464
|View full text |Cite
|
Sign up to set email alerts
|

InGaN/GaN Structures: Effect of the Quantum Well Number on the Cathodoluminescent Properties

Abstract: In this work we compare luminescence results obtained on InGaN/GaN multiple quantum well (QW) structures with 10 and 30 QWs. The aim is to increase the intensity of faster blue QW emission and decrease the luminescence of the QW defect band, showing a slower luminescence decay time, which is undesired for fast scintillator applications. We demonstrate that increasing the number of InGaN QWs is an efficient method to reach this goal. The luminescence improvement of the sample with higher number of QWs is explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Materials with a very sharp scintillating response in the sub-1 ns regime have been previously studied (Padilha et al 2013, Turtos et al 2016a and they are found in the form of semiconductor nanoplatelets (Turtos et al 2016c) or multiple quantum well heterostructures (Hospodková et al 2017). In this case the quantum confinement of electron-hole pairs plays a significant role in enhancing the matrix element for the radiative transition (Wilkinson et al 2004) and it is also responsible for one of the most interesting features of scintillating nanocrystals: biexcitons with a very high binding energy and therefore stable at room temperature (Grim et al 2014).…”
mentioning
confidence: 99%
“…Materials with a very sharp scintillating response in the sub-1 ns regime have been previously studied (Padilha et al 2013, Turtos et al 2016a and they are found in the form of semiconductor nanoplatelets (Turtos et al 2016c) or multiple quantum well heterostructures (Hospodková et al 2017). In this case the quantum confinement of electron-hole pairs plays a significant role in enhancing the matrix element for the radiative transition (Wilkinson et al 2004) and it is also responsible for one of the most interesting features of scintillating nanocrystals: biexcitons with a very high binding energy and therefore stable at room temperature (Grim et al 2014).…”
mentioning
confidence: 99%